Raanan Weitz (comp.). Urbanization and the Developing Countries, Report on the Sixth Rehovot Conference, Nueva York, [N.Y.], Editorial Praeger, 1973. 310 p. - Rodríguez y González, Alejandro (Estudios Demográficos y Urbanos, 1974)
RAANAN WEITZ (Comp.), Urbanization and the Developing Countries, Report on the Sixth Rehovot Conference, Nueva York, Editorial Praeger, 1973.